The Utilisation of Information Technology in Increasing Reading Interest in the Library of Sekolah Tinggi Teologi Imanuel (SETITEL) Telukdalam - Sunyianto, Sunyianto; Zakiah, Diana Mulida; Dao, Ose; Kerisman, Kerisman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study aims to determine the utilisation of information technology in increasing reading interest in the Library of Imanuel College (SETITEL) Telukdalam. The research method used is qualitative research. Data were collected using triangulation techniques, namely observation, interviews and documentation. Furthermore, the informants in this study were students of the Imanuel Theological College (SETITEL) Telukdalam with the characteristics of informants, namely 4th semester, 6th semester and 8th semester students totalling 6 people. The technique of taking informants using purposive sampling technique. The results of this study indicate that with the use of information technology in the Library of "SETITEL" Imanuel Telukdalam College, which plays an important role in supporting the management and planning of automated library development in order to improve the quality of library services effectively and efficiently, meet the information needs of the academic community and support the teaching and learning process, one of which is the OPAC service which can be used as a medium for finding the required information sources. In addition, with the existence of information technology as a strategy or effort to increase student interest in reading at the Imanuel Theological College (SETITEL) Telukdalam through the use of library services such as: special reading rooms, provision of digital services, interior design, exhibitions and provision of information retrieval systems or OPAC (Online public access catalog).